Competência informacional no Portal de Periódicos da Capes: uma análise a partir dos treinamentos de uso - Fernanda Gomes Almeida (2014)
Qualitative study aimed at assessing the impact of training in the use of the Capes Portal of E-Journals at the level of information literacy of students. The research starts with a review on the Portal Capes of E-Journals and the actions promoted by the UFMG University Library to promote access to and use of the Portal information resources. Next, the research presents a theoretical framework about information literacy, information searching and construction of search strategies. The survey sample was formed, in the first stage - pre-instruction test, by 14 students who enrolled voluntarily in a training program offered by the university library to the UFMG community. After the pre-instruction test, the students went through an instructional session. In the second stage of the research, post-instruction test and interviews, seven of the 14 students present at the initial stage participated. Data collection was conducted through observation with computer screen recording in the pre-instruction test and, two weeks after (post-instruction test), observation with screen recording and interviews. Data were obtained and analyzed based on the second standard of the ACRL Information Literacy Competency Standards for Higher Education. Results led to the conclusion that participation in training sessions positively influences the development and achievement of information literacy.